Isle of blood and stone - Lucier, Makiia (Houghton Mifflin Harcourt, 2018)
When two maps surface, each bearing the same hidden riddle, nineteen-year-old Elias, a royal mapmaker, sets sail with King Ulises to uncover long-held secrets behind the mysterious disappearance of the king's two young brothers eighteen years earlier.